2019
DOI: 10.14309/ajg.0000000000000170
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation With Lactoferrin and Lysozyme Ameliorates Environmental Enteric Dysfunction: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: INTRODUCTION: Environmental enteric dysfunction (EED) predisposes children throughout the developing world to high rates of systemic exposure to enteric pathogens and stunting. Effective interventions that treat or prevent EED may help children achieve their full physical and cognitive potential. The objective of this study is to test whether 2 components of breast milk would improve a biomarker of EED and linear growth during the second year of life. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 78 publications
0
17
0
1
Order By: Relevance
“…While some benefits have been observed with bovine lactoferrin supplementation, even more success has been shown when lactoferrin is used in combination with other biological agents. For instance, children supplemented with lactoferrin and lysozyme, another component of breast milk observed to improve gut health, experienced decreased hospitalization and reduced development of acute malnutrition [48] . In another study with lactoferrin in combination with Lactobacillus GG, infants with intervention showed a decreased incidence of severe necrotizing enterocolitis [49] .…”
Section: Discussionmentioning
confidence: 99%
“…While some benefits have been observed with bovine lactoferrin supplementation, even more success has been shown when lactoferrin is used in combination with other biological agents. For instance, children supplemented with lactoferrin and lysozyme, another component of breast milk observed to improve gut health, experienced decreased hospitalization and reduced development of acute malnutrition [48] . In another study with lactoferrin in combination with Lactobacillus GG, infants with intervention showed a decreased incidence of severe necrotizing enterocolitis [49] .…”
Section: Discussionmentioning
confidence: 99%
“…Identifying components of breast milk that protect children from diarrhea in the first six-months of life may offer the opportunity to supplement beyond this period and provide extended protection to older children. A recently published study of bovine and recombinant human lactoferrin and lysozyme reported no significant effect on lactulose excretion [53]. However, the intervention did reduce the incidence of malnutrition and hospitalization in the included children.…”
Section: Prevention and Managementmentioning
confidence: 95%
“…In addition, lactoferrin has demonstrated the capacity to protect from methotrexate induced barrier dysfunction in rats 26 . Particularly intriguing is a recent report that suggests that lactoferrin improves barrier function in the context of environmental enteropathy 27 .…”
Section: Development and Broad Administration Of New Therapeutics Capmentioning
confidence: 99%